Clinically relevant radioresistant cells exhibit resistance to HO by decreasing internal HO and lipid peroxidation - Kazuo Tomita; Yoshikazu Kuwahara; Yuko Takashi; Kento Igarashi; Taisuke Nagasawa; Hideki Nabika; Akihiro Kurimasa; Manabu Fukumoto; Yoshihiro Nishitani; Tomoaki Sato (Tumor Biology)
Radiation therapy is one of the choices to treat malignant tumors. In radiation therapy, existence of radiation-resistant cell is a major problem to overcome. We established clinically relevant radioresistant cells that had been obtained by exposing to 2 Gy/day X-rays for more than 30 days. These cells are resistant to 2 Gy/day X-ray exposure and anticancer agents. However, the underlying resistance mechanism remains unclear. We investigated the resistance of clinically relevant radioresistant cells to hydrogen peroxide (H 2 O 2 ), confirming a degree of resistance. Neither catalase enzyme activity nor aquaporins appeared to be involved in H 2 O 2 resistance. Mitochondrial DNA copy number, adenosine triphosphate (ATP) concentration, and plasma membrane potential were decreased. The timing of H 2 O 2 intake was delayed and lipid peroxidation was decreased. Sensitivity of clinically relevant radioresistant cells to H 2 O 2 was enhanced by 1-palmitoyl-2-(5′-oxo-valeroyl)-sn-glycero-3-phosphocholine administration. These results suggest that the membrane status is a major factor conferring H 2 O 2 resistance in clinically relevant radioresistant cells, and we should further investigate how membrane status could be used to enhance the therapeutic effect on cancer.